Factors differentially associated with early readmission at a university teaching psychiatric hospital. Issue 4 (10th March 2015) - Hamilton, Jane E.; Rhoades, Howard; Galvez, Juan; Allen, Melissa; Green, Charles; Aller, Mildred; Soares, Jair C.
Abstract Rationale, aims and objectives The rate of psychiatric readmissions within 30 days of discharge is a well‐established behavioural health system performance measure linked to the quality of inpatient hospital care as well as to access to community‐based aftercare services. The purpose of this study was to examine the factors differentially associated with earlier readmission among a sample of patients (n = 588) readmitted within 30 days of discharge to a university teaching psychiatric hospital from 2001 to 2010. Methods Quality assurance interviews were conducted with patients readmitted within 30 days of discharge. The interview data were merged with clinical symptom and electronic medical record data. Multinomial logistic regression analysis was used to examine readmission within 7 days and from 8 to 14 days compared with 15–30 days after discharge while controlling for socio‐demographic and treatment variables previously associated with psychiatric readmission. Results Multiple clinical, treatment and patient‐reported factors were differentially associated with earlier readmission. In particular, lack of engagement in post‐discharge aftercare services was a strong predictor of earlier readmission. Conclusions Strategies are needed to improve patients' transition from inpatient psychiatric hospitalization to aftercare services. Psychiatric hospitals attempting to reduce very early readmissions should seek to implement innovative transitional care initiatives targeting both patient and treatment factors.